Expressão das células supressoras derivadas da linhagem mielóide (MDSC’S) e sua relação com os níveis de IL-10, IL-13, IFN-γ e VEGF em pacientes adultos portadores de síndromes mielodisplásicas - Mota, Anacélia Gomes de Matos (2021)
An inflammatory process aims to restore the homeostasis of the injured tissue through the activation of innate and acquired immunity. As the inflammation process proceeds, several cells are stimulated and recruited resulting in an immune response with the participation of inflammation mediators. Another important group of cells participating in the inflammatory process is formed by suppressor cells derived from the myeloid lineage (MDSC's). Knowledge about the role of MDSC’s in hematological diseases is still poorly understood. The pathogenesis of myelodysplastic syndrome (MDS) is complex and multifactorial and depends on the interaction between hematopoietic cells and their microenvironment. Objective: To evaluate cell expression (MDSC's) and correlate them with serum levels of IL-10, IL-13, IFN-γ and VEGF in adult MDS patients, correlate them with clinical variables. Methods: 93 patients with MDS de novo were included (2 MDS with del 5q; 2 Unclassifiable MDS, 11 MDS-DU, 18 MDS AS; 23 MDS-EB and 37 MDS-DM) according to WHO classification and IPSS-R. 50 healthy volunteers were included as a control group. Interleukin analyzes were quantified by ELISA. The phenotyping of MDSC's cells was performed by labeling with monoclonal antibodies and evaluated by flow cytometer-FACSVerse. Results: There was a predominance of 55.9% females among the patients. The mean age in this group was 72.4 years. Patients with MDS showed significantly higher serum levels of IL-10, IL-13, IFN-γ and VEGF than the control group. (p<0.001) There was no significant expression of MDSC’s cells when compared to the control group (p=0.0388). The expression of MDSC’s cells was significantly higher in male patients with MDS than in female patients (p=0.041). As for the IPSS-R, there was a significant association between the expression of MDSC’s in high and very high risk patients when compared with those categorized as very low, low and intermediate risk according to IPSS-R (p=0.011). It was observed that the expression of PMN-MDSC’s cells was significantly higher in patients with MDS than in the control group (p<0.001). As for risk stratification, there was a significant association of PMN-MDSC’s expression between high and very high-risk patients than in patients categorized as very low, low and intermediate risk according to IPSS-R. (p=0.041). The expression of M-MDSC's was significantly higher in MDS patients compared to controls (p<0.001). By Spearman's correlation, it was observed: a moderate, positive and significant correlation between IL-10 and IL-13 production (r=0.564; p<0.001); a positive and significant correlation between IL-10 and IFN-y production (r=0.252; p=0.04); a positive correlation between IL-10 and VEGF (r=0.275; p<0.001); a significant negative correlation between IL-10 and serum ferritin level (r=-0.410; p<0.001); a significant correlation between IL-13 and INF-γ levels (r=0.239; p=0.007); a positive correlation between IFN-γ and VEGF with r=0.253 and p=0.004; a positive and significant correlation between VEGF and neutrophils, with r=0.233 and p=0.028. Conclusion: The results of this study demonstrate the importance of the relationship between MDSC’s and the secretion of inflammatory cytokines in the pathogenesis of MDS. Through these results, it is likely that MDSC's cells act in the inflammatory process as part of the pathogenesis of MDS and may constitute future therapeutic targets.